The Urgency and Function of the Islamic Religious Education Curriculum as a System of Learning - Aulia, Ridha; Fitri, Laila Annisa (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2024)
This study aims to determine the meaning, urgency, and function of the education curriculum, especially Islamic religious education. This research uses library research with data analysis using descriptive content analysis. The results show that the curriculum is very important to understand related to its meaning, urgency, and function. In general, the function and urgency of the curriculum in Islamic religious education as a learning plan so that it can run systematically for both educators, students, and schools. The curriculum for students has a function to be directed in the learning process, neatly structured material can make students achieve meaningful and useful learning for their future lives. The function of the curriculum for educators is as a reference in the teaching process. The function of the curriculum for Madrasah/school is to be used as a reference for actions related to learning activities, especially Islamic Religious Education lessons.